Comparison of esthetic smile perceptions among male and female Indonesian dental students relating to the buccal corridors of a smile - Astriana Nurfitrah; C. Christnawati; Ananto Ali Alhasyimi (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: A smile constitutes a form of measurement as to whether or not an orthodontic treatment has proved successful. A smile is said to be ideal if a balance exists between the shape of the face and teeth. One benchmark used to assess the quality of an ideal smile is that of buccal corridors. These are formed of the black space between the lateral edge of maxillary posterior teeth and the corner of the lip which appears during the action of smiling. Evaluating the contrasting perceptions of male and female smiles based on buccal corridor aspects is considered important to identifying the specific qualities an ideal smile. Purpose: The purpose of this study was to determine the difference between the perceptions of an ideal smile held by Indonesian dental students of both genders based on buccal corridors. Methods: A total of 36 dental students, equally divided between male and female students and ranging in age from 18-21 years old, were enrolled in this study. The smiles of all subjects were photographed from the front for later assessment by the subjects themselves. Assessment was undertaken twice, with a two-week interval between the first and second, by comparing subjects’ photographs with reference pictures of buccal corridors. Data gathered were analyzed by using kappa-statistic and U-Mann Whitney. Results: The results indicated that all the subjects showed a good level of coincidence in their analysis (κ=0.76). Statistical analysis showed that the score of 0.123 (p>0.05) was shown in U-Mann Whitney. Conclusion: Indonesian male and female dental students have the same perception of an aesthetic smile with regard to its buccal corridor.